Evaluation of the antiproliferative effect of histone deacetylase inhibitor (HDACi) CI-994 and Liposomal Cisplatin LipoPlatin on MCF-7 and MDA-MB-231 cells as monotherapy and combined therapy: Evaluation of CI-994 and LipoPlatin on MCF-7 and MDA-MB-231 cells - Çetin, İdil; Topçul, Mehmet R. (Cellular and Molecular Biology, 2025)
In this study, the effects of histone deacetylase inhibitor CI-994 and nanotechnological drug liposomal cisplatin LipoPlatin on Luminal A breast cancer and triple-negative breast cancer were explored using agents alone and in combination. MCF-7 and MDA-MB-231 cell lines were used. Cell viability, and cell index values obtained from xCELLigence System, MI, BrdU LI and AI were evaluated in experiments. In monotherapy applications, 10 μM, 20 μM and 40 μM concentrations of CI-994 and 80 μM, 160 μM, and 250 μM concentrations of LipoPlatin were applied to both cell lines. IC50 concentration of CI-994 was 10 μM for both cell lines. While IC50 concentration of LipoPlatin was 80 μM for Luminal A breast cancer cell line, this concentration was 160 μM for triple-negative breast cancer cell line. The application of a combination of CI-994 and Lipoplatin for each cell line has shown that while there was a significant decrease in cell viability, mitotic index (MI), and BrdU labeling index (LI), there was a significant increase in AI. Consequently, it was thought that combined treatments were more efficient than single medication applications and decreased the cell prognosis with a synergistic and additive impact.